The decision sampling framework: a methodological approach to investigate evidence use in policy and programmatic innovation. - Mackie, Thomas I.; Schaefer, Ana J.; Hyde, Justeen K.; Leslie, Laurel K.; Bosk, Emily A.; Fishman, Brittany.; Sheldrick, R. Christopher. (Tufts University. Tisch Library., 2021)
Keywords: Health care policy, Mental health care policy, Decision-making, Decision sciences, Evidence, Foster care.; Springer Open.